The development and the inter-rater agreement of a treatment protocol for vestibular/oculomotor rehabilitation in children and adolescents post-moderate-severe TBI. (10th November 2021) - Sorek, Gilad; Katz-Leurer, Michal; Gagnon, Isabelle; Chevignard, Mathilde; Stern, Nurit; Fadida, Yahaloma; Kalderon, Liran; Shaklai, Sharon; Schneider, Kathryn
ABSTRACT: Introduction: There is limited evidence investigating the effect of vestibular/oculomotor rehabilitation programs in children and adolescents post moderate-severe TBI at the sub-acute stage. Objective :To describe the development of a treatment protocol for vestibular/oculomotor interventions in this population, and to assess the inter-rater agreement of this protocol as an initial step of a clinical trial. Method :The protocol was developed by 10 health professionals, address the high variability of balance performance, the high prevalence of vestibular/oculomotor abnormalities and the low prevalence of symptoms reported in this population. Results :The protocol enables the clinician to use the assessment during the treatment exercise selection. The training position was defined by the Pediatric Balance Scale. Vestibular/oculomotor exercises were selected using a quantified version of the Vestibular/Ocular Motor Screening. The exercise protocol was selected based on impairment in function or reproduction of symptoms. The protocol planning was implemented by two assessors in 27 children and adolescents post-moderate-severe TBI (median age 14.1 [6–18.4] years) in the sub-acute stage (median 40 [14–162] days since injury). Very high agreement was found (k > 0.72) in all the parameters. Conclusion : This protocol could reliably be used in a randomized control trial that assesses the effect of vestibular/oculomotor rehabilitation program in children and adolescents post moderate-severe TBI at the sub-acute stage.